Industrial and Service Robotics Selected, peer reviewed papers from the 13th International Conference on Industrial, Service and Humanoid Robotics (ROBTEP 2014), May 15-17, 2014, High Tatras, Slovakia (Trans Tech Publications Ltd, 2014)
Collection of selected, peer reviewed papers from the 13th International Conference on Industrial, Service and Humanoid Robotics (ROBTEP 2014), May 15-17, 2014, High Tatras, Slovakia. Volume is indexed by Thomson Reuters CPCI-S (WoS).The 63 papers are grouped as follows: Chapter 1: Robotic Research and Application of Robots, Chapter 2: Automation of Production Processes Keyword: Robotics, Service Robots, Mobile Robots, Industrial Robots, Manufacturing Robotic Cell, Optimal Navigation, Intelligent Manufacturing Systems, Kinematic Structure The 63 papers first consider robotic research and applications of robots, then the automation of production processes. The topics include motion coordination of two robots in Cartesian space based on mechanical impedance, observation as a learning method in the simple visual system of vehicle control, materials having a high degree of adhesion for gripping elements designing, the chosen aspects of self-reconfigurable robots, accuracy control in machining low rigidity shafts, and implementing computer systems for supporting the technological preparation of production for technologies of surface processing. - Materials science- Mechanical engineering- Robotics